Notes on the Illegal Condition in the State of Extraction. How Not To Be an Informant - Moreiras, Alberto (Review of International American Studies, 2018)
We live, increasingly, in a state of extraction. My thesis is that we have not yet figured out the implications of a primary or fundamental logic of state extraction. We have not figured out its implications for our own predicament—for the predicament, that is, not of state functionaries as such, not of extractors and surveyors, which is a predicament of domination, but the predicament of those who would rather not be dominated, and who understand that giving up on domination is the logical price to be paid. These latter figures, those who refuse domination, those who prefer not to be dominated, hence not to dominate, they might in fact constitute the “borders of the border,” that fantastic fringe territory of the human this conference has decided to thematize and, in some sense, to honor. Let me then reserve that theoretical position, the position of border or hyperborder dwellers, to develop what follows. I will claim that the border of the border is today the site where information will not be shared—an opaque site of silence and secrecy, a place of radical reticence concerning unconcealment.